Building and legalizing a test to evaluate the time for the motor response time for skills advance and retreat foil fencer in fencing game - ALTOOHAFI, sajjad; Abdullah Falah, Alaa (Journal of Physical Education, 2023)
The study aimed of the research is to build a test time for the motor response to skills advance and retreat players for the foil fencer in the sport of fencing, and to learn about the digital values to test the time for the motor response time for skills advance and retreat skillful for the foil players in the sport of fencing, and deriving the criteria for testing the time for the motor response to the two skills of progress and retreat to evaluate Foil fencer players in the sport of fencing, and the descriptive approach relied on the foil fencer players in the sport of fencing from the emerging fencing clubs with ages under (15) years for the sports season (2022/2023), the total number of (67) players, all of whom were deliberately chosen in a comprehensive inventory by (100 %) to represent the total research sample, were chosen for the exploratory sample (6) players, and for the building sample (31) players, and the application sample (legalization) (30) players, The researchers concluded that the test of the speed of the motor response to the skills of progress and retreat achieved six standard levels by which the time of the speed of motor response to the skills of progress and retreat of the fencing players in the sport of fencing is evaluated. The fencing weapon in the sport of fencing, and the interest in providing the requirements for measuring the time of the motor response speed of the two skills of advancing and retreating for the players of the fencing weapon in the sport of fencing, as well as training the coaches on how to apply it in tracking the level of their players.